The relationship between the structure of firms’ human capital and corporate innovation performance - Huimin Shao; Qing Jin; Yihang Guo; Fei Zhou; Walton Wider; Liangyan Lu (PLoS ONE, 2025)
Innovation in enterprise development is undoubtedly important. The relationship between its structure and the formation of enterprise innovation factors is at the core, so it is crucial to clarify them. Therefore, based on data on A-share listed companies in China from 2007 to 2022, this paper adopts a multilevel structural equation model to explore the effect of the structure of human capital on enterprise innovation performance. Unlike prior studies, this paper divides innovation performance by enterprises into “substantive innovation” and “strategic innovation.” Our results show that human capital plays an important role in promoting both strategic and substantive innovation, which is achieved mainly by increasing technological intensity, investing more in R&D, and receiving more government subsidies. In addition, the heterogeneity test shows that this facilitating role is significant in both samples, divided into the criteria of firm ownership and compensation incentives. However, they have different degrees of influence. This provides empirical support for the response by Chinese enterprises regarding the national development strategy and their new ideas about cultivating high-quality technological innovation and achieving sustainable development.